The Three Cultures: Natural Sciences, Social Sciences, and the Humanities in the 21st Century - Kagan, Jerome (Cambridge University Press, 2012)
In 1959 C. P. Snow delivered his now-famous Rede Lecture, "The Two Cultures," a reflection on the academy based on the premise that intellectual life was divided into two cultures: the arts and humanities on one side and science on the other.